Pemahaman Dasar Akutansi dan Pajak di SMK TECHNO MEDIA, Buaran, Kec.Serpong, Kota Tangerang Selatan, Banten. - Baharuddin Saga; Muslim .; Agus Sudiyatmoko (CV. ITTC INDONESIA, 2025)
Techno Media Vocational High School is a school majoring in Broadcasting and Film that develops Editing and Broadcasting science so that understanding of the basics of accounting and tax is still very low. This problem will have an impact on students' ability to make personal and corporate financial decisions as well as entrepreneurial skills. This study aims to provide a basic understanding of accounting and tax at SMK Techno Media, South Tangerang City as a tool in decision making, by evaluating the level of students' understanding of the basics of accounting and tax, and identifying the factors that influence it. This study applies a qualitative method with data collection techniques in the form of interviews, observations, and literature studies by comparing the theories obtained from the basic understanding of accounting and tax. The results of this study indicate that students of SMK Techno Media, South Tangerang City, are very good at socializing the basic understanding of accounting andtax, this is observed in terms of enthusiasm and cooperation of SMK Techno Media students. Students' interest in socialization provides positive thingsin knowledge and practice of financial management up to tax reporting that must be done as Taxpayers. This can be useful for SMK Techno Media students in managing the budget for providing editing and broadcasting tools, information on making accurate financial reports, knowledge of tax and legal compliance, and preparing students to become independent professionals